مقاصد سُورة الإنسان وخَوَاصها: دراسةٌ حديثيةٌ تحليليةٌ: Objectives of Surah Al Insan and Critical Analysis of Ahadith Related to its Features - Shalash, Adnan (Al Basirah, 2023)
Surah Al-Insan was revealed to introduce the impact of many heavenly laws including the declaration of the status of man. It also mentions the creation of Adam and the blessings that the Almighty had bestowed upon His servants and His rulings in their creation. The surah opens by talking about the principle of creating man, providing him with the senses of hearing and sight, and guiding him to the path, then dividing humans into two categories: the thankful and the ungrateful, and talking about the reward of the thankful and the ungrateful, and describing Paradise and Hell. Then, it praises the deeds of the thankful, such as fulfilling a vow, providing food for the sake of God, and fearing the punishment of God Almighty, and it adds, by describing what they have with their Lord of heaven; reward, favor, and honor. Furthermore, it explains the source of the revelation of the Qur’an, and the Prophet - may God bless him and grant him peace – who commanded patience, remembrance of God Almighty, and would offer the night prayers. It also mentions something contained in the previous surah; It is Surah Al-Qiyamah, which talks about loving this immediate world and abandoning the afterlife and threatening them with replacing others like them if they persist in disbelief and stubbornness. Then the Noble Surah concludes by declaring that the Noble Qur’an is a reminder and admonition to all human beings, urging them to believe and act according to what it says.